2001
DOI: 10.1094/pdis.2001.85.2.189
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Bacterial Spot in Bell Pepper Induced by Acibenzolar-S-Methyl

Abstract: Bell pepper plants sprayed with the chemical acibenzolar-S-methyl (ABM, Actigard 50 WG) showed resistance to subsequent infections with the bacterial spot agent Xanthomonas axonopodis pv. vesicatoria. Induction of resistance was independent of the cultivar used, and was expressed as early as 3 days after treatment and continued for at least 2 weeks. In the field, applications of ABM every 2 weeks, alone or in combination with copper, resulted in disease control similar to the standard treatment of copper plus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
87
0
7

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(103 citation statements)
references
References 21 publications
9
87
0
7
Order By: Relevance
“…This was demonstrated in the two tests conducted here using acibenzolar-S-methyl and oxyetracycline. Our results are consistent with those of Paradela et al (2001) and Quezado-Duval et al (2005a) for tomato, and those of Romero et al (2001) for chili pepper. There is evidence that acibenzolar-S-methyl controls the disease by inducing plant resistance, but the product is implicated in reducing plant productivity (Godard et al, 1999;Dietrich et al, 2005).…”
Section: Discussionsupporting
confidence: 94%
“…This was demonstrated in the two tests conducted here using acibenzolar-S-methyl and oxyetracycline. Our results are consistent with those of Paradela et al (2001) and Quezado-Duval et al (2005a) for tomato, and those of Romero et al (2001) for chili pepper. There is evidence that acibenzolar-S-methyl controls the disease by inducing plant resistance, but the product is implicated in reducing plant productivity (Godard et al, 1999;Dietrich et al, 2005).…”
Section: Discussionsupporting
confidence: 94%
“…vesicatoria isolated from pepper fields 1993−1994 (Lee and Cho, 1996). These prompted the search for alternatives for bacterial disease control such as application of antimicrobial plant extracts and defense activator (Louwes et al, 2001;Romero et al, 2001;Seo et al, 2004). Although diverse applications have been tried to control bacterial spot and speck diseases, a few studies were conducted to figure out appropriate control methods of bacterial wilt disease of tomato plants.…”
mentioning
confidence: 99%
“…ASM was effective in inducing resistance to bacterial spot in bell pepper (Romero et al 2001). Further research is needed to evaluate rates, application timings, and the spectrum of disease control on bell pepper as well as crop safety.…”
Section: Discussionmentioning
confidence: 99%
“…Acibenzolar-Smethyl [ASM (Actigard 50WG, Syngenta Crop Protection] activates the systemic acquired resistance (SAR) pathway in plants. Romero et al (2001) demonstrated that triggering SAR was effective in reducing damage from bacterial spot on pepper and additionally ASM helped manage anthracnose (C. coccodes) on tomato (Abbasi et al 2002).…”
Section: Introductionmentioning
confidence: 99%